2009
DOI: 10.1245/s10434-008-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Considerations on Sentinel Node Biopsy in Melanoma from an Italian Multicentric Study on 1,313 Patients (SOLISM–IMI)

Abstract: Regression in the primary melanoma seems to be a protective factor from metastasis in the SLN. When correctly calculated, the SNB FN rate is 15-20%. Furthermore, the SNB is important to more precisely assess the prognosis of patients with melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 43 publications
10
81
2
9
Order By: Relevance
“…Furthermore, previous studies involving melanomas from all anatomic sites showed a statistically significant improvement in survival in patient with intermediate thickness melanomas (range, 1-4 mm), which suggests that some subgroups of patients may benefit from ELND 3,25,31 . Finally, despite the fact that sentinel lymph node biopsy (SLNB) has been adopted into clinical practice as reliable staging modality, there are lots of arguments against it, such as increased incidence of nodal (regional and in-transit) recurrence in sentinel lymph nodes (SLN) negative patients, possibility of false-negative results, difficult identification of SLN if they are located close to primary site, SLN found in multiple node fields in contrast to melanomas located on extremities which usually drain to only 1 field, SLN in parotid region which are often very small, may be difficult to find, and their removal may put the facial nerve at risk 8,10,12,15,16,29,36,37 . However, some authors reported that intraparotid SLN biopsy is a reliable, accurate, and safe procedure for staging cutaneous head and neck melanoma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies involving melanomas from all anatomic sites showed a statistically significant improvement in survival in patient with intermediate thickness melanomas (range, 1-4 mm), which suggests that some subgroups of patients may benefit from ELND 3,25,31 . Finally, despite the fact that sentinel lymph node biopsy (SLNB) has been adopted into clinical practice as reliable staging modality, there are lots of arguments against it, such as increased incidence of nodal (regional and in-transit) recurrence in sentinel lymph nodes (SLN) negative patients, possibility of false-negative results, difficult identification of SLN if they are located close to primary site, SLN found in multiple node fields in contrast to melanomas located on extremities which usually drain to only 1 field, SLN in parotid region which are often very small, may be difficult to find, and their removal may put the facial nerve at risk 8,10,12,15,16,29,36,37 . However, some authors reported that intraparotid SLN biopsy is a reliable, accurate, and safe procedure for staging cutaneous head and neck melanoma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of primary tumor ulceration, the sentinel lymph node was significantly more often positive than in the absence of ulceration [144,146,148,157].…”
Section: R Gutzmermentioning
confidence: 97%
“…Regression of the primary tumor either has not been correlated with sentinel lymph node positivity [144,165,166] or it has been correlated with lower sentinel lymph node positivity [148,167]. Primary tumor location plays no role in the indication for SLNB.…”
Section: R Gutzmermentioning
confidence: 99%
See 2 more Smart Citations